Comparison of buoyancy, passive and net active drag forces between Fastskin and standard swimsuits - Benjanuvatra, N.; Dawson, G.; Blanksby, B. A.; Elliott, B. C. (Journal of Science and Medicine in Sport, 2002)
A cross-sectional comparison between the buoyancy, passive and net active drag force characteristics of full-length, Fastskin swimsuits with that of standard swimsuits was completed with nine Open National level swimmers (5 males and 4 females). Subjects were weighed in a hydrostatic tank and then towed via a mechanical winch on the surface and 0.4 m deep at 1.6, 2.2 and 2.8 m/s. The subjects performed a prone streamlined glide and maximum effort flutter kick at each towing velocity and depth. Hydrostatic weight differences between swimsuit types were not significant (p> 0.05. Fastskin passive drag values were significantly less than normal swimsuits during surface towing at 1.6 and 2.8 m/s: and at 0.4 m deep towing at 1.6, 2.2 and 2.8 m/s. Net active drag force values also were lower for the Fastskin suits when compared with those of normal swimsuits and a significant difference existed for surface towing at all three velocities of 1.6, 2.2 and 2.8 m/s. The full-length, Fastskin swimsuits created less total hydrodynamic resistance than normal swimsuits while providing no additional buoyancy benefits.